Temperature control of essential oil extraction process using second generation of commande robuste d’ordre non entier (CRONE-2) / Nor Syafikah Pezol … [et al.] - Pezol, Nor Syafikah; Rahiman, Mohd Hezri Fazalul; Adnan, Ramli; Tajjudin, Mazidah (Universiti Teknologi MARA, 2021)
Steam distillation is one of the most popular methods used to extract the essential oils. Because of the behavior of aromatic plants that are volatile and fragile to excess heat, steam temperature needs to be regulated within a permissible range. Changes in the dynamics of steam temperature because of several factors such as variation of water level, capacity of loads, error in modelling and others had made the control effort more challenging. In fact, variation of parameters in plant models have interrupted the stability of the system and may jeopardize the quality of essential oils. In this paper, a CRONE controller which means Non-integer order robust controller will be applied to suppress the effect of variability in process parameter changes to the control loop. CRONE controller design pursued in frequency domain approach made it easier to achieve a constant transient within an iso-damping region. The CRONE performance will be compared with Internal Model Control PID with fractional-order Filter (IMCPID-FOF). The comparative study was done in time and frequency domain to reveal the robustness of the two controllers. It was shown that both controllers have good performance in time domain of closed-loop system where the desired percentage overshoot 5% ±3% are followed by system due to parameter of phase margin and gain crossover frequency. However, CRONE-2 has better performance while handling plant uncertainty with approximately 3% and 10% faster than IMC PID-FOF in rise time and settling time, respectively.